Gender Differences in Emotional Intelligence among Madrasah Students - Wilda Khanifatun; Ikhrom (Journal of Southeast Asian Islam and Society, 2025)
This study aims to analyze the level of emotional intelligence among students and to investigate gender differences in emotional intelligence among students at MTs Al Falah Margoyoso Jepara. Using a quantitative methodology with descriptive analysis, this research encompasses the entire student population of MTs Al Falah Margoyoso Jepara, totaling 288 students. Cluster random sampling was utilized to select a sample size of 70 participants. Data collection was conducted using a 55-item instrument, and data analysis was performed using descriptive analysis and t-tests. The findings of this study indicate that (1) the level of emotional intelligence among students is distributed as follows: 11.4% low, 38.6% moderate, 40% high, and 10% very high, which mean that the majority of students exhibit a high level of emotional intelligence. (2) Female students demonstrate a higher level of emotional intelligence compared to male students. (3) There is a statistically significant difference in the level of emotional intelligence between male and female students.